Enhancement of Magnetic Resonance Imaging with Metasurfaces. Issue 9 (11th January 2016) - Slobozhanyuk, Alexey P.; Poddubny, Alexander N.; Raaijmakers, Alexander J. E.; van den Berg, Cornelis A. T.; Kozachenko, Alexander V.; Dubrovina, Irina A.; Melchakova, Irina V.; Kivshar, Yuri S.; Belov, Pavel A.
Abstract : It is revealed that the unique properties of ultrathin metasurface resonators can improve magnetic resonance imaging dramatically. A metasurface formed when an array of metallic wires is placed inside a scanner under the studied object and a substantial enhancement of the radiofrequency magnetic field is achieved by means of subwavelength manipulation with the metasurface, also allowing improved image resolution.